Analysis of Logistics Management of Medical Equipment at RSU. Haji Medan - Harahap, Shelly Safira Maulia; Chairani, Nadila; Sinaga, Riantania; Dina, Dina; Zulaika, Talitha; Nurhasanah, Nurhasanah; Hasibuan, Rapotan (Universitas Ibn Khaldun Bogor, 2025)
Medical devices are tools and/or equipment used to prevent, diagnose, treat and reduce disease. The aim of this study was to assess how well medical equipment purchases balance hospital operations. The research method uses a descriptive-analytic approach and is qualitative in nature. The results of the research show that logistics management at RSU Haji Medan has been carried out well and in accordance with applicable procedures. The process of procuring medical equipment at Haji Medan Regional Hospital which follows the SOP system approach, finances, human resources and facilities still do not fully comply with the rules for managing medical devices in health facilities. Inadequate infrastructure, budgets that need to be increased, problems with process components that have not been received, and less than optimal use of medical equipment are just some of the weaknesses.